Parallelism in adaptive radiations of experimental Escherichia coli populations. (1st January 2016) - Saxer, Gerda; Travisano, Michael
Abstract: Adaptive radiations are major contributors to species diversity. Although the underlying mechanisms of adaptive radiations, specialization and trade‐offs, are relatively well understood, the tempo and repeatability of adaptive radiations remain elusive. Ecological specialization can occur through the expansion into novel niches or through partitioning of an existing niche. To test how the mode of resource specialization affects the tempo and repeatability of adaptive radiations, we selected replicate bacterial populations in environments that promoted the evolution of diversity either through niche expansion or through niche partitioning, and in a third low‐quality single‐resource environment, in which diversity was not expected to evolve. Colony size diversity evolved equally fast in environments that provided ecological opportunities regardless of the mode of resource specialization. In the low‐quality environments, diversity did not consistently evolve. We observed the largest fitness improvement in the low‐quality environment and the smallest the glucose‐limited environment. We did not observe a change in the rate of evolutionary change in either trait or environment, suggesting that the pool of beneficial mutations was not exhausted. Overall, the mode of resource specialization did not affect the tempo or repeatability of adaptive radiations. These results demonstrate the limitations of eco‐evolutionary feedbacks to affect evolutionary outcomes.